Enhanced detection of hepatitis B virus in Hong Kong blood donors after introduction of a more sensitive transcription‐mediated amplification assay. Issue 10 (22nd March 2013) - Tsoi, Wai‐Chiu; Lelie, Nico; Lin, Che‐Kit
Abstract : Background: A total of 517, 072 and 399, 326 consecutive donations were screened for hepatitis B virus (HBV) by individual‐donation nucleic acid testing (ID‐NAT) using Ultrio and Ultrio Plus assays (Novartis Diagnostics), respectively. The impact of more sensitive HBV detection by the latter assay version was established by comparing NAT yield and transmission risk. Study Design and Methods: Donations were screened simultaneously for HBV serologic markers and ID‐NAT, followed by discriminatory assay and confirmatory test algorithms. Window period (WP) reduction and residual HBV transmission risk were computed using mathematical modeling. Results: HBV NAT‐yield rates for both WP and occult HBV infection (OBI) increased significantly from 1:34, 471 to 1:17, 362 (p = 0.036) and from 1:5120 to 1:2450 (p < 0.0001), despite a 1.2‐ and 1.6‐fold decrease in hepatitis B surface antigen (HBsAg) incidence and prevalence rates respectively. After adjusting for this bias, the WP and OBI NAT‐yield improvement factors were 2.3 and 3.4, respectively, higher than a less than 1.5‐fold increase estimated from analytical sensitivity studies on HBV Genotype A and C standards. The current WP transmission risk with Ultrio Plus screening was estimated at 1:55, 000 compared to 1:22, 000 with HBsAg testing. Conclusion: The observed greater than twofold enhanced WP NAT yield with the Ultrio Plus assay can be explained by greater than 10‐fold increased analytical sensitivity in detecting the HBV Genotype B and C strains in Hong Kong. Direct comparison studies of the two assay versions on dilutions of HBV NAT‐yield samples are required to confirm this hypothesis.